Incident Syphilis Infections in an HIV Population: Presentation and Care. (4th October 2017) - Lang, Raynell; Read, Ron; Krentz, Hartmut; Gill, John
Abstract: Background: Syphilis is an emerging global health concern with an estimated 12 million new infections being documented annually. In individuals with HIV, syphilis presentations may be atypical leading to the recommendation for regular routine screening. This retrospective cohort study aimed to characterize syphilis presentation and serologic features in an HIV co-infected population. Methods: All incident syphilis infections (initial and repeat) occurring in HIV patients between 2006 and 2016 were identified via routine syphilis screening every four months during care at Southern Alberta HIV Clinic (SAC) and Calgary STI clinic (CSTI). Charts and databases were reviewed for each syphilis event. Data was pooled and statistical analysis performed. Results: We identified 361 infections, of which 250 cases met inclusion criteria in 195 different HIV patients (72% initial and 28% repeat infections). Infections were seen more commonly in men 227/250 (95%). Caucasians accounted for 72% of the population with 13% being within the African, Caribbean and Black community. The risk factors for HIV in patients with syphilis were MSM 76%, heterosexual activity 19% and intravenous drug use 4%. Over half (50.8%) of syphilis infections were asymptomatic and only identified through routine/risk based screening. Rash was the most common symptomatic presentation (23%), followed by skin lesions (18%). Those with repeat syphilis infections, not on ART and CD4 counts less than 200 cells/mm 3 were more likely to be symptomatic. Ten patients (4%) experienced CNS syphilis involvement and all presented with an initial RPR titer of 3 1:32. The RPR titers were higher among those with repeat syphilis infections (29% had titers over 1:256). Those with repeat episodes of syphilis usually had primary (28%), secondary (28%) or early latent disease (39%) and rarely late latent disease (3%). Since initiation of screening, the amount of late latent syphilis among our HIV patients has decreased from 50% to 4.4%. Conclusion: Syphilis infection was most often asymptomatic in our HIV positive population and occurred predominantly in MSM. Our findings stress the importance of regular syphilis screening among high-risk populations. Disclosures: All authors: No reported disclosures.